Application of circulating tumour DNA in terms of prognosis prediction in Chinese follicular lymphoma patients - Zhao, Mengjing; Li, Qingjuan; Yang, Jing; Zhang, Min; Liu, Xiaolan; Zhang, Hongwei; Huang, Yunpeng; Li, Jing; Bao, Jiangping; Wang, Jingfang; Du, Jun; Guan, Tao; et al. (Frontiers in Genetics, 2023)
Background. Follicular lymphoma (FL), an indolent non-Hodgkin lymphoma (NHL), is generally incurable. Favourable prognosis and durable remission are crucial for FL patients. The genetic mutation spectrum provides novel biomarkers for determining the prognosis of FL patients, but its detection is easily affected by the collection of tumour tissue biopsies. In this study, we aimed to describe the mutational landscape of FL using circulating tumour DNA (ctDNA) samples and to explore the relationship between mutations and prognostic indicators of clinical outcome in patients with newly diagnosed follicular lymphoma and the prognostic value of such mutations. Methods. A total of 28 patients with newly diagnosed FL were included in this study. A targeted NGS-based 59-gene panel was used to assess the ctDNA mutation profiles. Differences in clinical factors between patients carrying mutations and those without mutations were analysed. We also explored the relationship between gene mutation status, mean VAFs (variant allele frequencies) and clinical factors. The Kaplan‒Meier method was applied to analyse the overall survival (OS) and progression-free survival (PFS) of patients carrying mutations and those without mutations. Results. ctDNA mutations were detectable in 21 (75%) patients. The most commonly mutated genes were CREBBP (54%, 15/28), KMT2D (50%, 14/28), STAT6 (29%, 8/28), CARD11 (18%, 5/28), PCLO (14%, 4/28), EP300 (14%, 4/28), BCL2 (11%, 3/28), and TNFAIP3 (11%, 3/28), with a mutation frequency of >10%. Patients with detectable ctDNA mutation tended to present with advanced Ann Arbor stage (III-IV) (p=0.009), high FLIPI risk (3-5) (p=0.023) and severe lymph node involvement (No. of involved areas ≥5) (p=0.02). In addition, we found that the mean VAF was significantly higher in patients with advanced Ann Arbor stage, high-risk FLIPI, elevated lactate dehydrogenase (LDH: 0-248U/L), advanced pathology grade, bone marrow involvement (BMI) and lymph node involvement. Additionally, KMT2D, EP300, and STAT6 mutations were associated with inferior PFS (p<0.05). Conclusion. We described the ctDNA mutation landscapes in Chinese patients with newly diagnosed FL and found that ctDNA VAF means reflect tumour burden. Moreover, PFS was shorter in patients with KMT2D, EP300 and STAT6 mutations.